2023
DOI: 10.3390/electronics12132933
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Signal-Based Real-Time Emotion Recognition Based on Exploiting Mutual Information with Physiologically Common Features

Abstract: This paper proposes a real-time emotion recognition system that utilizes photoplethysmography (PPG) and electromyography (EMG) physiological signals. The proposed approach employs a complex-valued neural network to extract common features from the physiological signals, enabling successful emotion recognition without interference. The system comprises three stages: single-pulse extraction, a physiological coherence feature module, and a physiological common feature module. The experimental results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It has been observed that researchers mostly utilize the SVM classifier for carrying out classification tasks. Moreover, deep machine learning techniques improve classification accuracy [26][27][28][29][30][31][32][33][34]. Various studies have employed deep neural networks to automatically extract features and classify data.…”
Section: Related Workmentioning
confidence: 99%
“…It has been observed that researchers mostly utilize the SVM classifier for carrying out classification tasks. Moreover, deep machine learning techniques improve classification accuracy [26][27][28][29][30][31][32][33][34]. Various studies have employed deep neural networks to automatically extract features and classify data.…”
Section: Related Workmentioning
confidence: 99%